Comparison of Simultaneous Distillation and Extraction, Static Headspace and Headspace-Solid Phase Microextraction Coupled with GC/MS to Measure the Flavour Components of Tricholoma matsutake - Qin Chen, Xuan; Qian Wang, Qian; Ming Li, Jun; Qin Wang, Ya; Zhong Zhang, Xue; Zhi Li, Kun (Asian Journal of Chemistry, 2013)
Simultaneous distillation and extraction, static headspace assay and headspace-solid phase microextraction combined with GC/MS, were optimized to analyze flavour compounds in Tricholoma matsutake. The optimal conditions for simultaneous distillation and extraction were as following: sample/solution 6:8 (w:v), incubation 1 h, 90 ºC distillation 2 h, 1 min extraction. The optimal conditions for static headspace assay were 130 ºC equilibrium 30 min. For headspacesolid phase microextraction, the best conditions were 80 ºC equilibrium 5 min, PDMS fibers extraction. 52, 27 and 27 flavour compounds can be identified by the improved simultaneous distillation and extraction, static headspace assay and headspace-solid phase microextraction, respectively. The analytical results from headspace-solid phase microextraction were similar to those from simultaneous distillation and extraction, of which 14 flavour compounds were also found in simultaneous distillation and extraction. Headspace-solid phase microextraction and simultaneous distillation and extraction were partly overlapped. While only 7 compounds from static headspace assay can also be detected in headspace-solid phase microextraction and simultaneous distillation and extraction. Twenty compounds unidentified in headspace-solid phase microextraction and simultaneous distillation and extraction can be detected in static headspace assay. Therefore, we suggested that the complementation and combination of improved static headspace assay and headspace-solid phase microextraction were applied to the analysis of flavour compounds in T. matsutake due to its efficiency and simplicity.